The nature of occupational unemployment rates in the United States: hysteresis or structural? - Bertrand Candelon; Arnaud Dupuy; Luis Gil-Alana (Institute for the Study of Labor (IZA), 2008)
This paper provides new evidence on the nature of occupational differences in unemployment dynamics, which is relevant for the debate between the structural or hysteresis hypotheses. We develop a procedure that permits us to test for the presence of a structural break at unknown date. Our approach allows the investigation of a broader range of persistence than the 0/1 paradigm about the order of integration, usually implemented for testing the hypothesis of hysteresis in occupational unemployment. In almost all occupations, we find support for both the structuralist and the hysteresis hypotheses, but stress the importance of estimating the degree of persistence of seasonal shocks along with the degree of long-run persistence on raw data without applying seasonal filters. Indeed hysteresis appears to be underestimated when data are initially adjusted using traditional seasonal filters.
urn:nbn:de:101:1-2008070279
Keywords: E24; 330; Occupational unemployment; structuralist; hysteresis; structural break; fractional integration; Arbeitslosigkeit; Beruf; Strukturelle Arbeitslosigkeit; Hysteresis; Strukturbruch; Schätzung; USA